Predicting Response of Constructed Tunnel to Adjacent Excavation with Dewatering - Panpan Guo; Feifei Liu; Gang Lei; Xian Li; Cheng-wei Zhu; Yixian Wang; Mengmeng Lu; Kang Cheng; Xiaonan Gong (Geofluids)
This paper proposes a new method for predicting the displacement and internal force of constructed tunnels induced by adjacent excavation with dewatering. In this method, the total excavation-induced additional stress on the constructed tunnel is derived by superposing the additional stresses induced by excavation unloading and dewatering effects. The additional stress induced by unloading effect is calculated using Mindlin’s solution. The additional stress induced by dewatering effect is calculated using the principle of effective stress and the Dupuit precipitation funnel curve. With the beam on elastic foundation method, the total additional stress is then used for calculating the tunnel displacement and internal force caused by adjacent excavation with dewatering. Based on three well-documented case histories, the performance of the proposed method is verified. Moreover, a parametric analysis is also performed to capture the effects of excavation depth, tunnel-to-excavation distance, initial water level, excavation plan view size, and specific yield on the responses of the constructed tunnels. The results indicate that the effect of excavation depth on the tunnel maximum vertical displacement, maximum bending moment, and maximum shear force is more significant at an excavation depth greater than the cover depth of the constructed tunnel. The tunnel maximum vertical displacement, maximum bending moment, and maximum shear force decrease nonlinearly with an increase in the tunnel-to-excavation distance and the initial water level. Among the investigated parameters, the excavation dimension in the tunnel longitudinal direction affects most the tunnel responses. The effect of specific yield on the tunnel displacement and internal force induced by adjacent excavation with dewatering becomes more obvious as increasing the initial water level and excavation depth.